Embryonal Rhabdomyosarcoma of the Oesophagus in a Young Dog. Issue 1 (January 2017) - Devriendt, N.; Van Brantegem, L.; Willems, A.; Raes, E.; de Rooster, H.
Summary: A 15-month-old great Dane dog, showing clinical signs related to hypertrophic osteopathy, was diagnosed radiographically with a mass in the region of the thoracic oesophagus. Exploratory thoracotomy revealed an extensive, highly vascularized and locally invasive oesophageal mass and the presence of nodules in adjacent lung lobes. The dog was humanely destroyed intra-operatively. Histological examination revealed that the mass was an embryonal rhabdomyosarcoma. This is the first report of rhabdomyosarcoma of the oesophagus of a dog. Rhabdomyosarcoma should be considered a differential diagnosis when a mass adjacent to the oesophagus is diagnosed.